Waist circumference in overweight and obese children - PAJUELO, JAIME (2004)
Objective: To determine children with additional risk consisting in visceral fat increase. Material and Methods: The study was carried out at Uripa district (Apurímac), Trujillo (La Libertad), and Lima public schools. The population studied consisted in 1234 children 6 through 10 year-old; 48,6% were female. Weight, height and waist circumference (WC) were done in all children and body mass index (BMI) was calculated with the first ones. BMI values were analyzed with Must et al classification, identifying overweight and obesity when BMI was 85 through 95 and above 95 percentiles, respectively. Waist circumference values were analyzed using Freedman and McCarthy tables. Results: Prevalence of overweight and obesity were 16,5 and 13,9%, respectively. Overall, overweight and obesity decreased with increasing age. The percentage of children with WC above 90 percentile increases with age in overweight and obese children. Average WC was slightly higher than in both UK and USA children. Conclusions: Over fifty percent of overweight and obese children appeared to have an additional risk if their WC was above normal. Risks could imply future cardiovascular problems if corrective actions are not taken immediately.